Design of an educational platform based on an innovative model of research in secondary school students - Andrade-Arenas, Laberiano; Corzo-Zavaleta, Janet Ivonne; Alvarado-Paucar, Ada; Baldeón-Vilca, Cecilia; Segovia-Fernández, Luis; Reyes-Vilca, Nelly; López-Tolentino, Giovana; Villarreal-Chumbes, Verónica; Canturín-Narrea, Jhon (Institute of Advanced Engineering and Science, 2025)
The development of research skills worldwide is more emphasized in postgraduate programs; however, the training of these skills should be carried out from basic education; that is, from elementary school. In this sense, this research aims to formulate a proposal to develop research skills in secondary school students through an innovative model. The methodology was carried out through student surveys and interviews with teachers and authorities. The ATLAS.ti 22 software was used for network analysis and SPSS 23 for statistical analysis. The results obtained in the survey show that the dimensions of reading comprehension, writing and argumentation, academic writing, and scientific writing are within the acceptable average. However, in the interviews, some students show difficulties in scientific writing, but they show a critical position in their arguments. It is concluded that the authorities should incorporate the proposed model of research skills in the curricular plan, adding it to their annual plan; for this purpose, teachers should be trained to transmit it to their students. In addition, an innovative model is proposed during the 5 years of high school studies to develop students' research skills. The beneficiaries of the proposal are the entire educational community and therefore the country.